THE INFLUENCE OF WORDWALL MEDIA IN ENHANCING LEARNING MOTIVATION OF FIRST-GRADE STUDENTS AT SD ISLAM PLUS YLPI PEKANBARU - putri yani; Febrina Dafit (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Technological advances require the world of education to innovate in creating interesting and interactive learning. One of the media that can be used to increase student learning motivation is Wordwall, a digital platform based on educational games. This study aims to determine the effect of using Wordwall media on the learning motivation of class I C students of SD IP YLPI Pekanbaru. The method used is quantitative with a quasi-experimental design of the Nonequivalent Control Group Design type. The research sample consisted of two classes: class IC as the experimental group (29 students) and class IB as the control group (29 students), which were selected through purposive sampling techniques. The research instrument was a Likert scale questionnaire consisting of 20 statement items and pretest and posttest tests to measure student learning motivation. The results of the independent sample t-test showed that there was a significant difference between the average student learning motivation before and after treatment. The average posttest score of the experimental class was 85.41, while the control class only reached 72.76. The results of the analysis showed a significance value of Sig. (2-tailed) = 0.000 <0.05, which means Ha is accepted and H0 is rejected. Thus, the use of Wordwall media has a significant influence in increasing students' learning motivation.